Die ewige geheime Geschichte des Geistes: Überlegungen zu Jacob Taubes und zur politischen Theologie - Poppenberg, Gerhard (Philosophische Rundschau, 2024)
Jacob Taubes was both a rabbi and a philosopher. His book Abendländische Eschatologie (1947) earned him academic reputation throughout the world. After having teached at Hebrew University, Princeton, Yale and Columbia University, he founded in the 1960s both an institut for jewish studies and an institut for philosophical hermeneutics at Freie Universität Berlin. Although his written work was rather small, Taubes, a genius of critical dialogue, was in touch with the main currents of intellectual life in the USA, France and Germany, discussing with Scholem problems of jewish messianism, with Marcuse questions of revolution and Carl Schmitt the stakes of political theology. Muller's intellectual biography shows ihm as a kind of prism which allows to recognize important discussions of modern philosophy, political theory and theology.